Performance analysis of SiRe next-generation sequencing panel in diagnostic setting: focus on NSCLC routine samples. Issue 1 (2nd October 2018) - Pepe, Francesco; De Luca, Caterina; Smeraglio, Riccardo; Pisapia, Pasquale; Sgariglia, Roberta; Nacchio, Mariantonia; Russo, Maria; Serra, Nicola; Rocco, Danilo; Battiloro, Ciro; Ambrosio, Francesca; Gragnano, Gianluca; et al.
Abstract : Aims: Following the development for liquid biopsies of the SiRe next-generation sequencing (NGS) panel that covers 568 clinical relevant mutations in EGFR, KRAS, NRAS, BRAF, cKIT and PDGFRa genes, in this current study, we apply this small NGS panel on tissue samples of lung cancer. Methods: A total of 322 specimens were prospectively tested. Technical parameters were analysed on both cytological and histological samples. In a subset of 75 samples, the EGFR SiRe results were compared with those generated by the European Community (CE)–IVD EGFR assay on Idylla platform. Clinical outcomes of 11 patients treated, on the basis of SiRe results, were also evaluated. Results: Only 28 (8.7%) specimens failed to produce a library; out of the 294 remaining samples, a total of 168 somatic mutations were found. In nearly all instances (74/75–99%), the EGFR SiRe results were confirmed by Idylla. In general, SiRe analytical parameters were excellent. However, histological and cytological specimens differed in relation to average reads for sample, mean number of mapped reads, median read length and average reads for amplicon. Treatment outcome evaluation in 11 patients showed a partial response in 82 % (9/11) patients with a median progression-free survival of 340 days. Conclusions: The small gene panel SiRe is a clinically relevant tool useful to widespread the adoption of NGS in predictive molecular pathology laboratories.